Editorial Note Vol.11(1) (The Lumbini Journal of Business and Economics, 2023)
The Lumbini Banijya Campus' Department of Research and Development (DRD) has been unwaveringly committed to elevating the region’s research quality. The publication of Vol. XI, No.1 issue of "The Lumbini Journal of Business and Economics (Special Issue)" is a testament to the DRD's unwavering dedication in this regard. The issue has been crafted to meet the contemporary needs of the business and economic environment in Nepal.The journal’s editorial board extends its sincere appreciation to the contributors of the International Seminar on Redefining Management Education in Nepal for their invaluable research papers and insightful comments, which added vitality to the journal. Furthermore, the editorial board is thankful to the President of the Campus Management Committee, Mr. Motilal Pandey, the Campus Chief, Prof. Dr. Tara Prasad Upadhyaya, and the faculty, staff, and students of Lumbini Banijya Campus for their invaluable support in shaping the final version of the issue.The Vol. XI, No. 1 issue comprises twenty-six research papers of diverse perspectives catering to Nepal's current business and economic environment. Although the editorial board has endeavored to eliminate all errors, it acknowledges that mistakes are inherent to the human condition. Therefore, the editorial board is receptive to constructive feedback as a positive means to improve the journal in future editions.In conclusion, the editorial board acknowledges and extends its sincere gratitude to all members for their tireless support in bringing the Vol. XI, the No. 1 issue to fruition, hopes the journal will provide insightful contributions to business and economics. Editor-in-chief April 2023